Turk-Life in India - Gupta, Neha; Martin, David; Hanrahan, Ben; O'Neill, Jacki (Proceedings of Group 2014, 2014)
Previous studies on Amazon Mechanical Turk (AMT), the most well-known marketplace for microtasks, show that the largest population of workers on AMT is U.S. based, while the second largest is based in India. In this paper, we present insights from an ethnographic study conducted in India to introduce some of these workers or ‘Turkers’ – who they are, how they work and what turking means to them. We examine the work they do to maintain their reputations and their work-life balance. In doing this, we illustrate how AMT’s design practically impacts on turk-work. Understanding the ‘lived work’ of crowdwork is a valuable first step for technology design.